Lipoic acid uiO-66 / amphiphilic tocnf composite film and method of making and use thereof

CN122898009APending Publication Date: 2026-10-13HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611363898.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-13

Smart Images

  • Figure CN122898009A_ABST
    Figure CN122898009A_ABST
Patent Text Reader

Abstract

The application discloses a lipoic acid UiO-66 / amphiphilic TOCNF composite film and a preparation method and application thereof. The preparation method comprises the following steps: modifying TOCNF by using 2-octenyl succinic anhydride to obtain amphiphilic TOCNF; dispersing the amphiphilic TOCNF in water, adding a zirconium source, an organic ligand and lipoic acid, and stirring and reacting at room temperature to prepare a lipoic acid UiO-66 / amphiphilic TOCNF composite material; and mixing and uniformly dispersing the lipoic acid UiO-66 / amphiphilic TOCNF composite material, a film forming agent and a plasticizer to perform film forming treatment to prepare the lipoic acid UiO-66 / amphiphilic TOCNF composite film. The lipoic acid UiO-66 / amphiphilic TOCNF composite film has pH and humidity dual response characteristics, can realize the controlled release of lipoic acid according to the change of a storage environment, and thus enhances the environmental adaptability and functional exertion stability of the system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of postharvest preservation technology of fruits and vegetables, and relates to a lipoic acid@UiO-66 / amphiphilic TOCNF composite film, its preparation method and application, and particularly to a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response, its preparation method and application. Background Technology

[0002] Fresh fruits are widely popular due to their rich nutritional content and excellent flavor. However, during harvesting, transportation, and storage, fruits are susceptible to mechanical damage, oxidation, and microbial contamination, leading to quality decline and even spoilage, severely impacting their shelf life and economic value. Therefore, developing efficient, safe, and environmentally friendly preservation technologies is crucial for maintaining fruit quality and reducing resource waste. Currently, common fruit preservation technologies include wax coating, low-temperature refrigeration, modified atmosphere packaging, and plastic packaging films. While these methods can slow down spoilage to some extent, they generally suffer from high operating costs, high energy consumption, heavy environmental burden, or lack of antioxidant and antibacterial functions. In recent years, biomass-based preservation coatings have attracted attention due to their biodegradability and environmental friendliness, especially the application of cellulose materials forming a protective film on the fruit surface. However, existing cellulose materials still have limitations in structural stability, active ingredient loading capacity, and environmental response regulation, making it difficult to meet the demands for precise controlled release and multiple protective functions under complex storage environments. In addition, some biomass preservation coating materials have limited interfacial compatibility and adhesion stability with the fruit surface, which can easily lead to peeling or uneven coverage during storage, affecting the sustainability of the preservation effect.

[0003] On the other hand, metal-organic frameworks (MOFs), as a novel porous material, have attracted attention in the field of active molecule loading due to their high specific surface area and tunable pore structure. However, MOFs are usually in powder form, which limits their processing and molding performance, and they are prone to problems such as uneven dispersion or unstable interfacial bonding in composite systems. Therefore, how to construct a composite material system with stable structure, good interfacial bonding, and the ability to achieve multi-environmental response regulation is a key technical direction in this field. In summary, it is necessary to develop a novel composite material system with stable structure, strong interfacial bonding, multi-environmental response characteristics, and the ability to achieve effective loading and controlled release of lipoic acid, in order to improve fruit preservation and meet the needs of green and environmentally friendly applications. Summary of the Invention

[0004] The main objective of this invention is to provide a thioctic acid@UiO-66 / amphiphilic TOCNF composite film, its preparation method and application, in order to overcome the shortcomings of the prior art.

[0005] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: This invention provides a method for preparing a thioctic acid@UiO-66 / amphiphilic TOCNF composite film, comprising: TOCNF was modified with 2-octenylsuccinic anhydride to obtain amphiphilic TOCNF; The amphiphilic TOCNF was dispersed in water, then a zirconium source was added and stirred at room temperature. An organic ligand and lipoic acid were then added and stirred at room temperature to prepare a lipoic acid@UiO-66 / amphiphilic TOCNF composite material. The mass ratio of the amphiphilic TOCNF to the zirconium source was 1:2 to 1:3, the molar ratio of the zirconium source to the organic ligand was 1:1 to 1:3, and the molar ratio of the lipoic acid to the zirconium source was 0.5:1 to 5:1. Furthermore, the lipoic acid@UiO-66 / amphiphilic TOCNF composite material, film-forming agent, and plasticizer are mixed and dispersed evenly to form a film-forming solution. Then, the film-forming solution is subjected to film-forming treatment by casting method to obtain a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response.

[0006] The present invention also provides a pH / humidity responsive thioctic acid@UiO-66 / amphiphilic TOCNF composite film prepared by the aforementioned method.

[0007] This invention also provides the application of the aforementioned pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film in fruit and vegetable preservation.

[0008] This invention also provides a method for preserving fruits and vegetables, comprising: Provide the film-forming solution used in the aforementioned preparation method; In addition, the film-forming solution is at least coated onto the surface of the fruit or vegetable, dried, and then stored.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses amphiphilic TOCNF as a substrate and constructs a UiO-66 loaded structure through in-situ growth to form a composite system with stable interface bonding. Compared with the traditional physical mixing method, the in-situ construction method improves the dispersion uniformity and structural stability of UiO-66 in the cellulose substrate and avoids particle agglomeration and interface peeling problems. (2) By modifying the cellulose material with amphiphilic properties, the present invention enhances the interfacial affinity of the composite material to the fruit surface, improves the adhesion stability and coverage uniformity of the coating on the fruit surface, and is conducive to improving the sustainability of the preservation treatment. (3) The present invention utilizes the porous structure of UiO-66 to encapsulate thioctic acid. The prepared thioctic acid@UiO-66 / amphiphilic TOCNF composite film has dual pH and humidity response characteristics, and can regulate the release of thioctic acid according to changes in the storage environment, thereby enhancing the environmental adaptability and functional stability of the system. Attached Figure Description

[0010] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0011] Figures 1a-1c The images show the scanning electron microscope morphology, water contact angle, and Fourier transform infrared spectra of TOCNF and amphiphilic TOCNF in Example 1, respectively. Figure 2 Fourier transform infrared spectra of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention. Figure 3 The present invention provides X-ray diffraction patterns of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5. Figures 4a-4e The graph shows the antibacterial and antioxidant properties of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention. Figure 5 The hemolysis rate diagram shows the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention. Figure 6 The encapsulation efficiency results of the UiO-66 / amphiphilic TOCNF and thioctic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention are shown in the figure. Figures 7a-7b The humidity-responsive release performance and pH-responsive release performance of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1 are shown respectively. Figures 8a-8bAtomic force microscopy (AFM) images, scanning electron microscopy (SEM) images, and cross-sectional SEM images of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1. Figures 9a-9b The image shows the application results of the UiO-66 / amphiphilic TOCNF and thioctic acid@UiO-66 / amphiphilic TOCNF composite coatings prepared for Comparative Example 1 and Example 1 on strawberries and bananas. Detailed Implementation

[0012] In view of the deficiencies of the prior art, the applicant, through long-term research and extensive practice, has proposed the technical solution of this invention. The technical solution of this invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0013] Specifically, as one aspect of the technical solution of this invention, the method for preparing a thioctic acid@UiO-66 / amphiphilic TOCNF composite film includes: TOCNF was modified with 2-octenylsuccinic anhydride to obtain amphiphilic TOCNF; The amphiphilic TOCNF was dispersed in water, then a zirconium source was added and stirred at room temperature. An organic ligand and lipoic acid were then added and stirred at room temperature to prepare a lipoic acid@UiO-66 / amphiphilic TOCNF composite material. The mass ratio of the amphiphilic TOCNF to the zirconium source was 1:2 to 1:3, the molar ratio of the zirconium source to the organic ligand was 1:1 to 1:3, and the molar ratio of the lipoic acid to the zirconium source was 0.5:1 to 5:1. Furthermore, the lipoic acid@UiO-66 / amphiphilic TOCNF composite material, film-forming agent, and plasticizer are mixed and dispersed evenly to form a film-forming solution. Then, the film-forming solution is subjected to film-forming treatment by casting method to obtain a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response.

[0014] In this invention, the amphiphilic TOCNF in the lipoic acid@UiO-66 / amphiphilic TOCNF composite material forms a continuous network structure with hydrophilic groups such as carboxyl groups and hydrophobic segments of octenyl groups on its surface. When the ambient humidity increases, the amphiphilic TOCNF can adsorb water and undergo a certain degree of swelling, promoting water penetration into the material interior, thereby accelerating the diffusion and release of active ingredients in the composite structure. Under lower humidity conditions, the material structure is relatively dense, and the release rate of active ingredients decreases, thus exhibiting humidity-responsive release characteristics. Lipoic acid is not only loaded in the porous structure of UiO-66, but may also form coordination with the UiO-66 zirconium cluster through its sulfur-containing groups, thereby improving the fixation efficiency of active ingredients in the carrier. When the ambient pH decreases, the H in the system... + As the concentration increases, the coordination between zirconium clusters and lipoic acid weakens, and some Zr-S coordination bonds dissociate, leading to the gradual release of lipoic acid originally fixed in UiO-66. Simultaneously, under acidic conditions, the interaction between guest molecules and the framework within the UiO-66 pores weakens, further promoting the diffusion of lipoic acid outward from the pores. Therefore, as the ambient pH decreases, the release rate of lipoic acid in the material increases, exhibiting a significant pH-responsive release characteristic. Furthermore, the hygroscopic swelling behavior of amphiphilic TOCNF is coupled with the porous mass transfer structure of UiO-66 to jointly construct a multi-level response system of "fiber network-porous framework," achieving synergistic regulation of lipoic acid release behavior. This allows the material to dynamically adjust the release rate of active ingredients according to changes in the fruit and vegetable storage environment, thereby improving preservation effects and the utilization efficiency of active ingredients. During strawberry storage, as the fruit ripens and microorganisms grow, the local humidity on the fruit surface increases, while acidic metabolites are produced in the spoilage area, leading to a decrease in the pH of the microenvironment. The material of this invention can sense the above-mentioned environmental changes and increase the release rate of lipoic acid, thereby releasing more active ingredients when the risk of fruit spoilage increases, achieving a preservation effect of release on demand.

[0015] In some preferred embodiments, the preparation method specifically includes: diluting the TOCNF suspension with water, adding 2-octenyl succinic anhydride solution and adjusting the pH to 8.0-9.0, then stirring the reaction at 20-30°C for 1-2 hours, and then adjusting the pH to 5.5-6.5 to terminate the reaction; finally, the obtained system is subjected to precipitation, centrifugation, washing, freeze-curing, and freeze-drying to obtain amphiphilic TOCNF.

[0016] Furthermore, the mass ratio of 2-octenylsuccinic anhydride to TOCNF is 2.5~7:100.

[0017] The amphiphilic TOCNF in this invention has abundant carboxyl groups and other active groups on its surface, which can interact with zirconium ions, providing a favorable interface for the formation of UiO-66, promoting the uniform dispersion of UiO-66 on the surface of cellulose nanofibers, and improving the structural stability of the composite material. UiO-66 has a large specific surface area and abundant pore structure, which can effectively improve the loading capacity of active ingredients such as lipoic acid. The amphiphilic TOCNF constructs a continuous network structure, which can further enhance the stable distribution of UiO-66 in the system, thus facilitating the uniform loading and continuous release of active ingredients. The amphiphilic TOCNF has both hydrophilic groups and hydrophobic segments, which can enhance the wettability and adhesion stability of the composite material on the surface of fruits and vegetables, improve the interfacial bonding ability between the composite material and the surface of fruits and vegetables, thus facilitating the continuous preservation effect of active ingredients. The hygroscopic expansion characteristics of amphiphilic TOCNF combined with the porous structure of UiO-66 can regulate the diffusion and release behavior of active ingredients according to changes in environmental humidity and pH, realizing the responsive release of preservation active ingredients, improving the utilization efficiency of active ingredients and the preservation effect of fruits and vegetables.

[0018] In some preferred embodiments, the preparation method specifically includes: dispersing the amphiphilic TOCNF in water and stirring at 40-50°C for 12-24 hours, then adding a zirconium source and stirring at 20-30°C for 3-5 hours, then adding an organic ligand and thioctic acid and stirring at 20-30°C for 10-12 hours, so that UiO-66 is generated in situ on the surface of the amphiphilic TOCNF and thioctic acid is loaded, thereby obtaining a system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material.

[0019] Furthermore, the zirconium source includes any one or more combinations of zirconium oxychloride octahydrate, zirconium tetrachloride, zirconium oxynitrate, and zirconium nitrate, preferably zirconium oxychloride octahydrate.

[0020] Furthermore, the organic ligand includes terephthalic acid.

[0021] Furthermore, the mass ratio of the amphiphilic TOCNF to the zirconium source is 1:2.35.

[0022] In this invention, lipoic acid mainly undergoes weak coordination with unsaturated zirconium sites in UiO-66 through its carboxyl group, while some lipoic acid is confined in the pores and interparticle spaces of UiO-66, thereby forming a stable loading state.

[0023] In some preferred embodiments, the preparation method specifically includes: A film-forming agent and a plasticizer were added to the system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material and stirred at 20~30℃ for 1~3h. After standing and degassing, a uniform film-forming solution was obtained. Furthermore, the film-forming solution is cast into a film using a casting method, and then dried to obtain a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response.

[0024] Furthermore, the mass-to-volume ratio of the film-forming agent to the system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material is 1~2g:100mL.

[0025] Furthermore, the mass-to-volume ratio of the plasticizer to the system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material is 1~2g:100mL.

[0026] Furthermore, the film-forming agent includes any one or more combinations of polyvinyl alcohol, chitosan, gelatin, sodium alginate, carboxymethyl cellulose, and hydroxypropyl methyl cellulose, preferably polyvinyl alcohol.

[0027] Furthermore, the plasticizer includes any one or more combinations of glycerin, sorbitol, polyethylene glycol, and propylene glycol, preferably glycerin.

[0028] Furthermore, the temperature for static degassing is 20~30℃, and the time is 12~24h.

[0029] Furthermore, the drying process is carried out at a temperature of 40-50°C for 12-16 hours.

[0030] In some preferred embodiments, the method for preparing the thioctic acid@UiO-66 / amphiphilic TOCNF composite film includes the following steps: (1) A 1.5 wt% TOCNF suspension was diluted with deionized water and a uniform dispersion was obtained under stirring at room temperature. A 2-octenyl succinic anhydride (OSA) solution was added to the dispersion, and the pH of the system was adjusted to 8.0–9.0 using sodium hydroxide. The reaction was stirred at room temperature. After the reaction was completed, the pH of the system was adjusted to 5.5–6.5 using hydrochloric acid to terminate the reaction. Ethanol was added to the resulting reaction system for precipitation, followed by centrifugation and washing with ethanol. The system was then rapidly frozen in liquid nitrogen to solidify quickly. Afterward, it was freeze-dried under vacuum until all moisture was removed, yielding dried amphiphilic TOCNF.

[0031] (2) The freeze-dried amphiphilic TOCNF was dispersed in deionized water and stirred to obtain a uniform dispersion system. Zirconium oxychloride octahydrate source was added to the above dispersion system and stirred at room temperature to allow zirconium ions to be uniformly dispersed on the amphiphilic TOCNF substrate. Organic ligands terephthalic acid and lipoic acid were added to the system simultaneously and stirred at room temperature to allow UiO-66 to be generated in situ on the surface of the amphiphilic TOCNF substrate, and to achieve the encapsulation of lipoic acid during the generation process.

[0032] (3) Add appropriate amounts of film-forming agent polyvinyl alcohol and plasticizer glycerin to the system obtained in step (2), stir at room temperature to disperse fully, and let stand to degas to obtain a uniform film-forming solution. Finally, at room temperature, cast the above solution into a film by casting method, and after drying, obtain lipoic acid@UiO-66 / amphiphilic TOCNF composite films with different proportions.

[0033] Preferably, in step (1), the 1.5 wt% TOCNF suspension is diluted with deionized water and a uniformly dispersed system is obtained under stirring conditions at room temperature. This is achieved by taking 33 ml of the 1.5 wt% TOCNF suspension and diluting it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. The stirring speed is 200~400 rpm, the temperature is 20~30℃, and the stirring time is 0.5~1 h.

[0034] Preferably, in step (1), the 2-octenyl succinic anhydride (OSA) solution is added to the dispersion system, and the pH of the system is adjusted to 8.0-9.0 with sodium hydroxide. The reaction is stirred at room temperature. The amount of OSA added is 2.5%-7% of the dry matter mass of TOCNF. The pH of the system is adjusted with a sodium hydroxide solution of 0.1 mol / L. After adjusting the pH of the system with sodium hydroxide, the stirring speed is 200-400 rpm, the temperature is 20-30℃, and the reaction time is 1-2 h.

[0035] Preferably, after the reaction described in step (1) is completed, the pH of the system is adjusted to 5.5~6.5 by hydrochloric acid to terminate the reaction. The pH of the system is adjusted by a hydrochloric acid solution with a concentration of 0.1 mol / L.

[0036] As a preferred embodiment, in step (1), ethanol is added to the obtained reaction system for precipitation treatment, followed by centrifugation and washing with ethanol. The volume fraction of ethanol is 95% (v / v). The centrifugation conditions are: speed of 10000~12000 rpm, temperature of 20~30℃, duration of 10~15 min, and ethanol washing 2~4 times.

[0037] Preferably, the step (1) involves rapid freezing in liquid nitrogen to solidify the material quickly; then, it is freeze-dried under vacuum until all moisture is removed to obtain dried amphiphilic TOCNF. The freeze-drying temperature is -80 to -60°C and the duration is 24 to 36 hours.

[0038] Preferably, in step (2), the amphiphilic TOCNF obtained by freeze-drying is dispersed in deionized water and stirred to obtain a uniform dispersion system. The amount of amphiphilic modified TOCNF obtained by freeze-drying is 0.263g, the stirring speed is 200~400rpm, the temperature is 40~50℃, and the duration is 12~24h.

[0039] As a preferred embodiment, in step (2), zirconium oxychloride octahydrate is added to the above dispersion system and stirred at room temperature to make zirconium ions uniformly dispersed on the amphiphilic TOCNF substrate. The amount of zirconium oxychloride octahydrate added is 0.618g, the stirring speed is 200~400rpm, the temperature is 20~30℃, and the duration is 3~5h.

[0040] Preferably, in step (2), organic ligands terephthalic acid and lipoic acid are added to the system simultaneously, and the mixture is stirred at room temperature to allow UiO-66 to be generated in situ on the surface of the amphiphilic TOCNF substrate, and lipoic acid is loaded during the generation process. The amount of terephthalic acid added is 0.638 g, the molar ratio of zirconium source to organic ligand is 1:1 to 1:3, and the molar ratio of lipoic acid to zirconium source is 0.5:1 to 5:1 (taking an amount of 0.618 g of zirconium source as an example, the amounts of lipoic acid added are 0.198 g / 0.396 g / 0.792 g / 1.188 g / 1.98 g respectively). The stirring speed is 200 to 400 rpm, the temperature is 20 to 30 °C, and the duration is 10 to 12 h.

[0041] As a preferred embodiment, in step (3), an appropriate amount of film-forming agent polyvinyl alcohol and plasticizer glycerin are added to the obtained system, and the mixture is stirred at room temperature to disperse it fully. The mass-volume ratio (g / mL) of the amount of polyvinyl alcohol and glycerin added to the total volume of the solution in the system is 1%~2%, the stirring speed is 200~400 rpm, the temperature is 20~30℃, and the stirring time is 1~3h.

[0042] Preferably, the static degassing in step (3) yields a uniform film-forming solution. Finally, at room temperature, the above solution is cast into a film by casting, and after drying, thioctic acid@UiO-66 / amphiphilic TOCNF composite films with different proportions are obtained. The static degassing temperature is 20~30℃ and the time is 12~24h, and the drying temperature is 40~50℃ and the time is 12~16h.

[0043] Another aspect of the present invention provides a pH / humidity responsive thioctic acid@UiO-66 / amphiphilic TOCNF composite film prepared by the aforementioned method.

[0044] Another aspect of the present invention provides the application of the aforementioned pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film in fruit and vegetable preservation.

[0045] Another aspect of the present invention provides a method for preserving fruits and vegetables, comprising: Provide the film-forming solution used in the aforementioned preparation method; In addition, the film-forming solution is at least coated onto the surface of the fruit or vegetable, dried, and then stored.

[0046] Furthermore, the storage temperature is 25°C and the humidity is 75%.

[0047] This invention involves diluting a 1.5 wt% TOCNF suspension with deionized water and obtaining a homogeneous dispersion system under stirring at room temperature. A 2-octenyl succinic anhydride (OSA) solution is added to the dispersion system, and the pH is adjusted to 8.0–9.0 using sodium hydroxide. The reaction is stirred at room temperature. After the reaction is complete, the pH is adjusted to 5.5–6.5 using hydrochloric acid to terminate the reaction. Ethanol is added to the resulting reaction system for precipitation, followed by centrifugation and washing with ethanol. The system is then rapidly frozen in liquid nitrogen to solidify quickly. Subsequently, it is freeze-dried under vacuum until all moisture is removed, yielding a dry amphiphilic TOCNF solid material. The freeze-dried amphiphilic TOCNF is dispersed in deionized water and stirred to obtain a homogeneous dispersion system. Zirconium oxychloride octahydrate (ZrO2) is added to the above dispersion system, and the mixture is stirred at room temperature to ensure uniform dispersion of zirconium ions on the amphiphilic TOCNF substrate. Organic ligands terephthalic acid and lipoic acid were simultaneously added to the system, and the mixture was stirred at room temperature to allow UiO-66 to form in situ on the surface of the amphiphilic TOCNF substrate, achieving encapsulation of lipoic acid during the formation process. Appropriate amounts of film-forming agent polyvinyl alcohol and plasticizer glycerol were added to the resulting system, and the mixture was stirred at room temperature to ensure thorough dispersion. After standing and degassing, a homogeneous film-forming solution was obtained. Finally, the solution was cast into films at room temperature using a casting method, and after drying, lipoic acid@UiO-66 / amphiphilic TOCNF composite films with different proportions were obtained.

[0048] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. This embodiment is implemented on the premise of the technical solution of the invention, and provides detailed implementation methods and specific operation processes. However, the protection scope of the present invention is not limited to the following embodiments.

[0049] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.

[0050] Example 1 This embodiment provides a method for preparing a pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film, specifically including the following steps: (1) Take 33 mL of 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniform dispersion system. Take 25 μL of 2-octenyl succinic anhydride (OSA) solution (corresponding to about 5%) and add it to the dispersion system. At the same time, adjust the pH of the system to 8.5 with 0.1 mol / L sodium hydroxide. Stir at 400 rpm for 1.5 h at room temperature. After the reaction is completed, adjust the pH of the system to 6.0 with 0.1 mol / L hydrochloric acid to terminate the reaction. Add three volumes of 95% ethanol solution to the obtained reaction system for precipitation treatment. Then centrifuge (12000 rpm, 25℃, 15 min) to separate and wash three times with 95% ethanol solution. It was then rapidly frozen in liquid nitrogen to solidify it quickly; subsequently, it was freeze-dried under vacuum for 24 hours until all moisture was removed, resulting in a dry modified amphiphilic TOCNF solid material.

[0051] (2) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 0.792 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 2:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0052] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then, allow it to stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain the thioctic acid@UiO-66 / amphiphilic TOCNF composite film of Example 1.

[0053] Example 2 This embodiment provides a method for preparing a pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film, specifically including the following steps: (1) Take 33 mL of 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniform dispersion system. Take 25 μL of 2-octenyl succinic anhydride (OSA) solution (corresponding to about 5%) and add it to the dispersion system. At the same time, adjust the pH of the system to 8.5 with 0.1 mol / L sodium hydroxide. Stir at 400 rpm for 1.5 h at room temperature. After the reaction is completed, adjust the pH of the system to 6.0 with 0.1 mol / L hydrochloric acid to terminate the reaction. Add three volumes of 95% ethanol solution to the obtained reaction system for precipitation treatment. Then centrifuge (12000 rpm, 25℃, 15 min) to separate and wash three times with 95% ethanol solution. It was then rapidly frozen in liquid nitrogen to solidify it quickly; subsequently, it was freeze-dried under vacuum for 24 hours until all moisture was removed, resulting in a dry modified amphiphilic TOCNF solid material.

[0054] (2) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 0.198 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 0.5:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0055] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain the thioctic acid@UiO-66 / amphiphilic TOCNF composite film of Example 2.

[0056] Example 3 This embodiment provides a method for preparing a pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film, specifically including the following steps: (1) Take 33 mL of 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniform dispersion system. Take 25 μL of 2-octenyl succinic anhydride (OSA) solution (corresponding to about 5%) and add it to the dispersion system. At the same time, adjust the pH of the system to 8.5 with 0.1 mol / L sodium hydroxide. Stir at 400 rpm for 1.5 h at room temperature. After the reaction is completed, adjust the pH of the system to 6.0 with 0.1 mol / L hydrochloric acid to terminate the reaction. Add three volumes of 95% ethanol solution to the obtained reaction system for precipitation treatment. Then centrifuge (12000 rpm, 25℃, 15 min) to separate and wash three times with 95% ethanol solution. It was then rapidly frozen in liquid nitrogen to solidify it quickly; subsequently, it was freeze-dried under vacuum for 24 hours until all moisture was removed, resulting in a dry modified amphiphilic TOCNF solid material.

[0057] (2) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 0.396 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 1:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0058] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain the thioctic acid@UiO-66 / amphiphilic TOCNF composite film of Example 3.

[0059] Example 4 This embodiment provides a method for preparing a pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film, specifically including the following steps: (1) Take 33 mL of 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniform dispersion system. Take 25 μL of 2-octenyl succinic anhydride (OSA) solution (corresponding to about 5%) and add it to the dispersion system. At the same time, adjust the pH of the system to 8.5 with 0.1 mol / L sodium hydroxide. Stir at 400 rpm for 1.5 h at room temperature. After the reaction is completed, adjust the pH of the system to 6.0 with 0.1 mol / L hydrochloric acid to terminate the reaction. Add three volumes of 95% ethanol solution to the obtained reaction system for precipitation treatment. Then centrifuge (12000 rpm, 25℃, 15 min) to separate and wash three times with 95% ethanol solution. It was then rapidly frozen in liquid nitrogen to solidify it quickly; subsequently, it was freeze-dried under vacuum for 24 hours until all moisture was removed, resulting in a dry modified amphiphilic TOCNF solid material.

[0060] (2) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 1.188 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 3:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0061] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain the thioctic acid@UiO-66 / amphiphilic TOCNF composite film of Example 4.

[0062] Example 5 This embodiment provides a method for preparing a pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film, specifically including the following steps: (1) Take 33 mL of 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniform dispersion system. Take 25 μL of 2-octenyl succinic anhydride (OSA) solution (corresponding to about 5%) and add it to the dispersion system. At the same time, adjust the pH of the system to 8.5 with 0.1 mol / L sodium hydroxide. Stir at 400 rpm for 1.5 h at room temperature. After the reaction is completed, adjust the pH of the system to 6.0 with 0.1 mol / L hydrochloric acid to terminate the reaction. Add three volumes of 95% ethanol solution to the obtained reaction system for precipitation treatment. Then centrifuge (12000 rpm, 25℃, 15 min) to separate and wash three times with 95% ethanol solution. It was then rapidly frozen in liquid nitrogen to solidify it quickly; subsequently, it was freeze-dried under vacuum for 24 hours until all moisture was removed, resulting in a dry modified amphiphilic TOCNF solid material.

[0063] (2) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 1.98 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 5:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0064] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain the thioctic acid@UiO-66 / amphiphilic TOCNF composite film of Example 5.

[0065] Comparative Example 1 (1) 0.263 g of the freeze-dried amphiphilic modified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the amphiphilic TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) was added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the amphiphilic TOCNF substrate.

[0066] (2) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain UiO-66 / amphiphilic TOCNF composite film.

[0067] Examples 1-5 and Comparative Example 1 were tested and characterized, and the results are as follows: Figures 1a-1c The images show the scanning electron microscope (SEM) morphology, water contact angle, and Fourier transform infrared (FTIR) spectra of the cellulose (TOCNF) prepared in Example 1 and the 2-octenyl succinic anhydride (OSA) modified TOCNF (cellulose). Figure 1a As shown, unmodified cellulose (TOCNF) exhibits a relatively loose three-dimensional network structure with interwoven fibers, numerous pores, and a generally loose morphology. After modification with 2-octenyl succinic anhydride (OSA), the microstructure of the resulting modified cellulose changes significantly. The fiber bundles are arranged more tightly, locally exhibiting a layered or lamellar stacked structure, with a reduced number of pores and improved structural density. This indicates that OSA modification can enhance the interaction between fibers and improve their structural density. Figure 1b As shown, the water contact angle of the unmodified cellulose surface is small, exhibiting strong hydrophilicity. After OSA modification, the water contact angle of the material surface significantly increases, indicating enhanced surface hydrophobicity. To characterize the modification effect of OSA on cellulose, Fourier transform infrared spectroscopy analysis was performed on unmodified cellulose (TOCNF) and modified cellulose. Figure 1c The results showed that unmodified cellulose at 1720 cm⁻¹ - An absorption peak exists near ¹, which can be attributed to the carbonyl stretching vibration in the carboxyl group. At 1680 cm⁻¹... -¹ A carbonyl-related absorption peak is also present near the cellulose surface, indicating that the oxidized cellulose surface contains a certain amount of carboxyl groups or other oxygen-containing functional groups. Compared with unmodified cellulose, the infrared spectrum of the modified sample shows significant changes. Specifically, at 2917 cm⁻¹... - A new absorption peak appears near ¹, which can be attributed to the stretching vibrations of the methylene and methyl groups. This absorption peak is not obvious in unmodified cellulose, but appears in the modified sample, indicating the introduction of aliphatic segments derived from OSA into the system, i.e., the modified cellulose surface has an increased nonpolar hydrophobic structure. Meanwhile, the modified sample shows an absorption peak at 1730 cm⁻¹. - An absorption peak appears near ¹, which can be attributed to the carbonyl stretching vibration in the ester group. This is in contrast to the absorption peak at 1720 cm⁻¹ in unmodified cellulose. - ¹Near carboxyl carbonyl absorption, 1730 cm⁻¹ - The appearance of the absorption peak near ¹ indicates the formation of a new ester group structure in the sample. Furthermore, the modified sample shows an absorption peak at 1232 cm⁻¹. - The absorption peak near ¹ can be attributed to the stretching vibration of the carbon-oxygen-carbon structure. This absorption peak is related to the carbon-oxygen bond vibration in the ester bond structure, and its appearance further indicates the formation of a new esterification linkage structure in the system. The above characteristic absorption peaks indicate that the hydrophobic segments and ester group structures in OSA have been successfully introduced into the cellulose system. Thus, the modified cellulose retains its original hydrophilic groups while introducing hydrophobic groups, giving it better amphiphilicity.

[0068] Figure 2 Fourier transform infrared (FTIR) spectra of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention. Comparative Example 1 is a UiO-66 / amphiphilic TOCNF composite film without lipoic acid loading; Examples 1-5 are lipoic acid@UiO-66 / amphiphilic TOCNF composite films with different ratios, wherein the molar ratio of lipoic acid to zirconium source is 2:1 (Example 1), 0.5:1 (Example 2), 1:1 (Example 3), 3:1 (Example 4), and 5:1 (Example 5), respectively. As shown in the figure, Comparative Example 1 has a wavelength of approximately 474 cm⁻¹. - A characteristic absorption peak appears at ¹, which can be attributed to the vibrational characteristics of the zirconium-oxygen bond, indicating that the UiO-66 structure was successfully constructed in the system. In Example 1, at approximately 1746 cm⁻¹... - The characteristic absorption peak of the carbonyl group appears at ¹, at 1310 cm⁻¹. - ¹ A characteristic absorption peak for carbon-oxygen bonds appears near 484 cm⁻¹, and at the same time, a characteristic absorption peak for carbon-oxygen bonds appears at approximately 484 cm⁻¹. - A vibrational absorption peak of the zirconium-oxygen bond was observed at ¹. Compared to Comparative Example 1, the characteristic absorption peak in the low wavenumber region of Example 1 decreased from 474 cm⁻¹. - ¹Moved to 484 cm- ¹ This indicates that the introduction of lipoic acid had a certain impact on the coordination environment of the zirconium-related structures in the system. Simultaneously, the appearance of characteristic absorption peaks of the carbonyl group and carbon-oxygen bond in Example 1 indicates the introduction of new oxygen-containing functional groups into the system. Combining the overall spectral changes of each example, it can be seen that the characteristic absorption peaks of the composite system changed after the introduction of lipoic acid, indicating that lipoic acid has participated in the construction of the composite system and interacted with each component, thereby forming a structurally stable multi-level composite system.

[0069] Figure 3 This invention presents X-ray diffraction patterns of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5. As shown in the figure, each sample exhibits a distinct broad and diffuse diffraction peak around approximately 20 degrees, indicating that the overall system is dominated by an amorphous structure based on a cellulose substrate. The diffraction peak of Comparative Example 1 is relatively flat, indicating that its structure is relatively loose. Compared with Comparative Example 1, the diffraction peak intensity and peak shape of each example after the introduction of lipoic acid are enhanced around approximately 20 degrees, indicating that the system structure is more compact. Further analysis shows that with the increase of lipoic acid addition, the diffraction peak position gradually shifts from 19.85 degrees in Comparative Example 1 to 19.37 degrees in Example 5, showing a trend of shifting to lower angles, indicating that the internal structure of the system is adjusted and the average spacing between molecular chains changes. Based on the system composition analysis, it is speculated that the introduction of lipoic acid enhanced the interactions between the components, affecting the arrangement of molecular chains to some extent, thus leading to a transformation of the structure from a relatively loose to a more compact and ordered state. Furthermore, with increasing lipoic acid content, shoulder peaks or sub-peaks gradually appear around 22 degrees, further indicating an improvement in the degree of order in the local structure of the system.

[0070] Figure 4a The images show the antibacterial properties of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention. Figures 4b-4c The graph shows the inhibition rate of the composite film against Escherichia coli and Staphylococcus aureus. Figures 4d-4e The graph shows the scavenging rates of DPPH (2,2-diphenyl-1-picrylhydrazyl radical) and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) radicals in the composite film. Figures 4a-4cAs shown, antibacterial performance tests indicated that the lipoic acid@UiO-66 / amphiphilic TOCNF composite film exhibited significant broad-spectrum inhibitory effects against both *Escherichia coli* and *Staphylococcus aureus*. Specifically, Example 1 showed inhibition rates of 99.49% against *Escherichia coli* and 96.81% against *Staphylococcus aureus*, respectively, demonstrating significantly superior antibacterial performance compared to the UiO-66 / amphiphilic TOCNF film in Comparative Example 1. This indicates that the lipoic acid loading significantly enhanced the antibacterial properties of the film. Figures 4d-4e As shown, with the increase of lipoic acid addition, the antioxidant properties of the composite films in each embodiment showed a significant upward trend. The film of Example 1 exhibited better free radical scavenging ability, with DPPH (2,2-diphenyl-1-picrylhydrazyl radical) and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) free radical scavenging rates reaching 76.55% and 66.17%, respectively. Both indicators were significantly higher than those of Comparative Example 1, indicating that the introduction of lipoic acid effectively enhanced the antioxidant capacity of the film.

[0071] Figure 5 The hemolysis rates of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention are shown. Biocompatibility evaluation results show that the hemolysis rates of all tested films range from 0.51% to 1.50%, which is significantly lower than the 5% biosafety threshold, indicating that the prepared composite films possess excellent blood compatibility. This result provides a reliable basis for its safety as a fruit surface preservation coating, proving that the material has good biosafety in direct contact with food surfaces.

[0072] Figure 6 The encapsulation efficiency of the UiO-66 / amphiphilic TOCNF and thioctic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Examples 1-5 of this invention is shown. Figure 6 As shown, the encapsulation efficiencies of the films in Examples 1-5 were 79.97%, 58.75%, 67.51%, 75.83%, and 72.78%, respectively. Overall, the encapsulation efficiency first increased and then slightly decreased with increasing thioctic acid loading, with Example 1 exhibiting the best encapsulation effect.

[0073] Figure 7a The graph shows the humidity-responsive release properties of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1. Figure 7bThe figure shows the pH-responsive release performance of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1. As shown in the figure, the film in Example 1 exhibits excellent dual-response release characteristics of humidity and pH, and can adapt to the slightly acidic environment (pH 5-6) and high humidity conditions (>85%RH) of post-harvest fruit storage. When the ambient humidity increased from 30% to 90%, the cumulative release of lipoic acid from the film in Example 1 increased significantly from 37.44% to 80% within 48 hours, showing a clear humidity-dependent release. This phenomenon can be attributed to the hydrophilic swelling effect of the lipoic acid@UiO-66 / amphiphilic TOCNF complex under high humidity conditions. At the same time, the film also exhibits significant acid-promoted release behavior, with the release of lipoic acid reaching 209.39 mg in an environment with a pH of 5.0, which is twice the release in a neutral environment (95.61 mg). This pH-responsive release behavior may be related to the coordination binding of lipoic acid with metal nodes in the UiO-66 framework, while the porous structure of the composite film and the amphiphilic TOCNF network regulate moisture and solvent diffusion, jointly promoting the pH-responsive release behavior. This dual-response mechanism enables the film to maintain basic release under high humidity conditions while accelerating the release of active ingredients in a slightly acidic environment, thereby prolonging the duration of action and reducing the risk of premature depletion, providing a controllable active substance delivery system for fruit surface preservation.

[0074] Figure 8a These are surface atomic force microscopy images of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1. Figure 8b Scanning electron microscope (SEM) images of the morphology and cross-sectional areas of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite films prepared in Comparative Example 1 and Example 1 are shown. Figure 8a As shown, in terms of three-dimensional surface morphology, the control group (OSA-modified TOCNF) film surface is relatively smooth with less undulation and lower roughness, indicating that the TOCNF matrix is ​​uniformly dispersed and forms a dense structure. The comparative example 1 film surface shows obvious granular protrusions and increased roughness, indicating that UiO-66 has been successfully loaded into the matrix, but there is a certain degree of agglomeration. After further introducing lipoic acid, the surface of the film in Example 1 exhibits a more pronounced peak-valley structure and significantly increased roughness, indicating that the interaction between lipoic acid@UiO-66 and TOCNF is enhanced, constructing a more complex microstructure. Figure 8bScanning electron microscopy (SEM) images showed that the control group had a dense and uniform surface, while a poorly dispersed particle structure was observed in Comparative Example 1. In contrast, the particles in Example 1 were smaller and more uniformly distributed, indicating that the introduction of lipoic acid effectively improved the dispersibility of UiO-66 in the matrix and enhanced interfacial compatibility. Figure 8b The cross-sectional scanning electron microscope images show that the control group has a dense and flat structure, Comparative Example 1 shows a certain degree of inhomogeneity, while Example 1 shows a more uniform and continuous dense structure with no obvious pores or phase separation.

[0075] Figures 9a-9b The figures show the application results of the UiO-66 / amphiphilic TOCNF and lipoic acid@UiO-66 / amphiphilic TOCNF composite coatings prepared in Comparative Example 1 and Example 1 on strawberries and bananas, respectively. The composite coating prepared in Example 1 showed a significant preservation effect in the storage experiment of strawberries and bananas.

[0076] Comparative Example 2 0.618 g of zirconium oxychloride octahydrate (1.92 mmol) was added to 100 mL of deionized water and dissolved by stirring at room temperature. Then, 0.638 g of terephthalic acid (3.84 mmol) and 0.792 g of lipoic acid (3.84 mmol) were added, and the mixture was stirred at room temperature for 12 h. After the reaction was completed, the product was collected by centrifugation and washed three times with deionized water to obtain LA@UiO-66 composite particles. 2 g of film-forming agent polyvinyl alcohol and 2 g of plasticizer glycerol were added to the obtained composite particles, and the mixture was stirred at 400 rpm for 2 h at room temperature to disperse it thoroughly. Subsequently, the mixture was allowed to stand at room temperature for 12 h to degas, resulting in a homogeneous film-forming solution. Finally, the solution was cast into a film at room temperature using a casting method, and dried at 45 °C to obtain a lipoic acid@UiO-66 composite film.

[0077] Comparative Example 3 (1) Take 33 ml of a 1.5 wt% TOCNF suspension and dilute it with 67 mL of deionized water to obtain a 0.5 wt% TOCNF suspension. Stir at 400 rpm for 0.5 h at room temperature to obtain a uniformly dispersed system. After thorough dispersion, freeze dry directly to obtain unmodified TOCNF without OSA grafting modification.

[0078] (2) 0.263 g of lyophilized unmodified TOCNF was dispersed in 100 mL of deionized water and stirred at 45 °C and 400 rpm for 24 h to obtain a uniform dispersion system. 0.618 g of zirconium source zirconium oxychloride octahydrate (1.92 mmol) was added to the above dispersion system and stirred at 400 rpm for 4 h at room temperature to uniformly disperse zirconium ions on the unmodified TOCNF substrate. 0.638 g of organic ligand terephthalic acid (3.84 mmol, molar ratio of zirconium source to organic ligand is 1:2) and 0.792 g of lipoic acid (molar ratio of lipoic acid to zirconium source is 2:1) were added to the system and stirred at 400 rpm for 12 h at room temperature to generate UiO-66 in situ on the surface of the unmodified TOCNF substrate and to achieve encapsulation of lipoic acid during the generation process.

[0079] (3) Add 2g of film-forming agent polyvinyl alcohol and 2g of plasticizer glycerin to the obtained composite system, and stir at 400 rpm for 2 hours at room temperature to fully disperse. Then let it stand at room temperature for 12 hours to degas and obtain a uniform film-forming solution. Finally, cast the above solution into a film at room temperature by casting, and dry it at 45°C to obtain a thioctic acid@UiO-66 / unmodified TOCNF composite film.

[0080] Comparative Example 4 Using the same zirconium source and organic ligand as in Example 1, UiO-66 particles were prepared without the addition of TOCNF and lipoic acid. 2 g of polyvinyl alcohol and 2 g of glycerol were added to the above dispersion system, and the mixture was stirred at 400 rpm for 2 hours at room temperature to ensure thorough dispersion, allowing the UiO-66 particles to be uniformly dispersed in the film-forming system. The solution was then allowed to stand at room temperature for 12 hours to degas, resulting in a homogeneous film-forming solution. Finally, the solution was cast into a film at room temperature using a casting method, and after drying at 45°C, a UiO-66 / polyvinyl alcohol composite film was obtained.

[0081] Test characterization: In an orchard in Anhui Province, China, fresh strawberries and bananas were carefully selected to ensure that the selected fruits were similar in shape, size, color, and ripeness, and free from obvious visual defects and diseases. After harvesting, the fruits were quickly transported to a laboratory for further processing. In the laboratory, the fruits were first thoroughly washed with distilled water and air-dried. Using the film-forming solutions from Example 1 and Comparative Examples 1-4, the strawberries and bananas were immersed in the film-forming solutions for 1 minute to ensure full saturation. They were then air-dried at room temperature in a fume hood for at least 60 minutes until the coating film was completely dry. The control group consisted of strawberries and bananas treated with a pure aqueous solution for 1 minute. The treated fruits were stored in an incubator at 25°C and 75% relative humidity. Samples were collected periodically on days 0, 2, 4, and 6, and various parameters, such as flesh color, firmness, weight loss, and decay rate, were measured and photographs were taken. Each group had three replicates, and all operations were performed at room temperature. The results are shown in Tables 1 and 2.

[0082] Table 1. Characterization results of the film-forming solutions prepared in Example 1 and Comparative Examples 1-4 after film formation on strawberries.

[0083] As shown in Table 1, after 6 days of storage, the brightness value and firmness of strawberries in the Example 1 treatment group were 36.51–38.81 and 39.47–44.11, respectively, both higher than those in the comparative examples. The weight loss rate and rot rate were 13.38–16.20% and 21.96–31.38%, respectively, both significantly lower, indicating that the coating film can effectively maintain the appearance and texture of the strawberries. The contact angle of Example 1 was 43.60–45.00°, lower than that in the comparative examples, indicating that the composite coating film has better wetting and spreading properties on the strawberry surface, which is conducive to forming a complete protective layer, corresponding to its lower weight loss rate. Meanwhile, its DPPH and ABTS removal rates reached 72.35–81.68% and 78.46–87.25%, respectively, significantly higher than those in the comparative examples, indicating that the coating film's strong antioxidant capacity can further slow down oxidative deterioration and spoilage during strawberry storage. This indicates that the combined effect of good interface coverage and antioxidant properties is the main reason why Example 1 effectively delayed the dehydration, softening and spoilage of strawberries.

[0084] Table 2. Characterization results of the film-forming solutions prepared in Example 1 and Comparative Examples 1-4 after film formation on bananas.

[0085] As shown in Table 2, after 6 days of storage, the brightness value and firmness of the bananas in the Example 1 treatment group reached 52.85–62.17 and 113.33–126.13, respectively, which were significantly better than the comparative examples, with a particularly outstanding effect in maintaining firmness. Meanwhile, the weight loss rate was only 6.45–7.13%, the lowest among all groups, indicating that the coating has a good inhibitory effect on banana ripening and softening, as well as moisture loss. The contact angle of Example 1 was 104.00–105.40°, lower than the comparative examples, indicating that the composite coating can improve its wetting and covering state on the banana surface; however, its contact angle was generally higher than that of strawberries, indicating that the interfacial behavior of the coating also differs due to the different surface characteristics of bananas. On the other hand, the rot rate in Example 1 decreased to 51.96–61.38%, while the DPPH and ABTS removal rates reached 70.42–80.68% and 77.35–86.42%, respectively, indicating that the strong antioxidant capacity, combined with the barrier effect of the coating, can delay the quality deterioration of bananas during storage. In summary, the composite coating's effects on bananas are mainly reflected in maintaining tissue firmness, reducing moisture loss, and delaying spoilage. The interfacial coverage and antioxidant effects work synergistically to improve the storage stability of bananas.

[0086] In addition, the applicant also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0087] It should be understood that the technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made to the technical solutions of the present invention without departing from the spirit and scope of the claims are within the scope of protection of the present invention.

Claims

1. A method for preparing a lipoic acid@UiO-66 / amphiphilic TOCNF composite film, characterized in that, include: TOCNF was modified with 2-octenylsuccinic anhydride to obtain amphiphilic TOCNF; The amphiphilic TOCNF was dispersed in water, then a zirconium source was added and stirred at room temperature. An organic ligand and lipoic acid were then added and stirred at room temperature to prepare a lipoic acid@UiO-66 / amphiphilic TOCNF composite material. The mass ratio of the amphiphilic TOCNF to the zirconium source was 1:2 to 1:3, the molar ratio of the zirconium source to the organic ligand was 1:1 to 1:3, and the molar ratio of the lipoic acid to the zirconium source was 0.5:1 to 5:

1. Furthermore, the lipoic acid@UiO-66 / amphiphilic TOCNF composite material, film-forming agent, and plasticizer are mixed and dispersed evenly to form a film-forming solution. Then, the film-forming solution is subjected to film-forming treatment by casting method to obtain a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response.

2. The preparation method according to claim 1, characterized in that, Specifically, it includes: The TOCNF suspension was diluted with water, and then 2-octenyl succinic anhydride solution was added to adjust the pH to 8.0-9.

0. The mixture was then stirred at 20-30°C for 1-2 hours, and the pH was adjusted to 5.5-6.5 to terminate the reaction. Finally, the obtained system was subjected to precipitation, centrifugation, washing, freeze-curing, and freeze-drying to obtain amphiphilic TOCNF.

3. The preparation method according to claim 2, characterized in that: The mass ratio of 2-octenyl succinic anhydride to TOCNF is 2.5~7:

100.

4. The preparation method according to claim 1, characterized in that, Specifically, it includes: The amphiphilic TOCNF was dispersed in water and stirred at 40-50°C for 12-24 hours. Then, a zirconium source was added and stirred at 20-30°C for 3-5 hours. Next, an organic ligand and thioctic acid were added and stirred at 20-30°C for 10-12 hours to generate UiO-66 in situ on the surface of the amphiphilic TOCNF and to encapsulate thioctic acid, thus obtaining a system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material.

5. The preparation method according to claim 4, characterized in that: The zirconium source includes any one or more combinations of zirconium oxychloride octahydrate, zirconium tetrachloride, zirconium oxynitrate, and zirconium nitrate; and / or, the organic ligand includes terephthalic acid. And / or, the mass ratio of the amphiphilic TOCNF to the zirconium source is 1:2.

35.

6. The preparation method according to claim 4, characterized in that, Specifically, it includes: A film-forming agent and a plasticizer were added to the system containing thioctic acid@UiO-66 / amphiphilic TOCNF composite material and stirred at 20~30℃ for 1~3h. After standing and degassing, a uniform film-forming solution was obtained. Furthermore, the film-forming solution is cast into a film using a casting method, and then dried to obtain a lipoic acid@UiO-66 / amphiphilic TOCNF composite film with pH / humidity response.

7. The preparation method according to claim 6, characterized in that: The mass-to-volume ratio of the film-forming agent to the system containing the thioctic acid@UiO-66 / amphiphilic TOCNF composite material is 1~2g:100mL; And / or, the mass-to-volume ratio of the plasticizer to the system comprising thioctic acid@UiO-66 / amphiphilic TOCNF composite material is 1~2 g: 100 mL; And / or, the film-forming agent comprises any one or more combinations of polyvinyl alcohol, chitosan, gelatin, sodium alginate, carboxymethyl cellulose, and hydroxypropyl methyl cellulose; and / or, the plasticizer comprises any one or more combinations of glycerol, sorbitol, polyethylene glycol, and propylene glycol; And / or, the temperature for static degassing is 20~30℃, and the time is 12~24h; And / or, the drying process is carried out at a temperature of 40~50℃ for a time of 12~16h.

8. A pH / humidity responsive thioctic acid@UiO-66 / amphiphilic TOCNF composite film prepared by the preparation method according to any one of claims 1-7.

9. The application of the pH / humidity responsive lipoic acid@UiO-66 / amphiphilic TOCNF composite film as described in claim 8 in the preservation of fruits and vegetables.

10. A method for preserving fruits and vegetables, characterized in that, include: Provide a film-forming solution as described in claim 1 or 6; In addition, the film-forming solution is at least coated onto the surface of the fruit or vegetable, dried, and then stored.